2023
DOI: 10.1111/add.16127
|View full text |Cite
|
Sign up to set email alerts
|

The association between maternal and paternal substance use and child substance use, internalizing and externalizing problems: a systematic review and meta‐analysis

Abstract: Aims There is substantial evidence showing an association between parental substance use and child substance use and/or mental health problems. Most research focuses upon maternal substance use, with the influence of paternal substance use often being overlooked. We aimed to investigate the differential effects of maternal and paternal substance use upon children aged 0–18 years. Methods We used systematic review methods to identify observational studies examining the association between either maternal or pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Research has shown that family services often focus upon mothers as the primary caregiver. Fathers are typically overlooked due to viewing them as less important to child outcomes ( Daniel and Taylor 2001 ), despite both father’s and mother’s alcohol use being found to be associated with adverse child mental health and substance use outcomes ( McGovern et al . 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that family services often focus upon mothers as the primary caregiver. Fathers are typically overlooked due to viewing them as less important to child outcomes ( Daniel and Taylor 2001 ), despite both father’s and mother’s alcohol use being found to be associated with adverse child mental health and substance use outcomes ( McGovern et al . 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also included the following self‐reported survey items collected at baseline from mothers (1981–83): cigarette smoking behaviours before pregnancy and in late pregnancy, cannabis use in the last 3 months of pregnancy, alcohol consumption before pregnancy and in late pregnancy, and binge drinking during pregnancy. These have previously been linked to the use of alcohol and other substances in children up to 18 years of age [28].…”
Section: Methodsmentioning
confidence: 99%
“…These have previously been linked to the use of alcohol and other substances in children up to 18 years of age [28].…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…A number of classic studies have shown that the risk of alcoholism runs in families (Anda et al, 2002;Cotton, 1979;Schuckit & Smith, 1996;Sher et al, 1991). More recent studies have corroborated these findings and extended them to a range of patterns of drinking, including drinking and intoxication frequency and Alcohol Use Disorders Identification Test (AUDIT) scores (Boden et al, 2019;Kendler, Ji et al, 2015;Mahedy et al, 2018;McGovern et al, 2023;). However, the existing studies on the association of parental alcohol use with alcohol use of their children focus on adolescence and the early twenties, and whether these associations extend to later adulthood is uncertain (Mahedy et al, 2018;.…”
mentioning
confidence: 89%